NSTP : National Development via National Service Training Program (CWTS 2) - Dela Cruz, Sonia Gasilla; Dela Cruz, Edeliza G.;Mapue, Paulino M. (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2015)
This book is a noble educational aim that is being undertaken by the NSTP 2 students during their outreach program. It is an effective tool utilized by higher education institutions to become familiarized with and responsive to the problems facing their constituencies.
1. Community needs assessment -- 2. Social mobilization -- 3. Community service -- 4. Community outreach program -- 5. Personality development -- 6. Issues and concerns in community outreach program -- 7. Environment development -- 8. Recreational activities -- 9. Summative evaluation.
Includes bibliographical references.
Keywords: COMMUNITY DEVELOPMENT -- NSTP -- CWTS